Strategi Pengembangan Daya Tarik Wisata Dalam Meningkatkan Kunjungan Wisatawan Lokal Di Kota Tua Jakarta : Tourism Attraction Development Strategy to Increase Local Tourist Visits in Jakarta's Old Town - Farah Munif; Frisiska; Liza Darwani (OGZ Research & Publishing, 2025)
This study examines ways to attract more tourists to Jakarta's Old Town, with the goal of increasing visitor numbers. In accordance with the policy stipulated in Law Number 10 of 2009, the tourism sector is a crucial aspect of the Indonesian economy. Jakarta's Old Town, rich in history and culture, is the focus of this study. In this study, a qualitative descriptive approach was used to identify potential, design strategies, and assess existing challenges. Tourism development focused on three main aspects: attractions, activities, and accessibility, as well as tourism products, reinforced by strategic theory and the role of government. From the findings of this study, it is hoped that an efficient development strategy can be formulated to capitalize on the unique history of Jakarta's Old Town. Cooperation from all relevant parties and professional management support are essential to achieve this. The primary goal is to increase visitor numbers while empowering local communities, preserving cultural heritage, and sustainably improving the local economy.